Development of ETS (E-Ticketing System) Module for Issue Management : Pembuatan Modul ETS (E-Ticketing System) untuk Manajemen Kendala - Syamsuddin, Muhammad; Indahyanti, Uce (Procedia of Engineering and Life Science, 2024)
This study proposes the integration of an Employee Tracking System (ETS) module within a logistics company's existing web application to streamline internal management processes. Focused on a one-month internship, the research aims to address the inefficiencies of conventional communication methods by facilitating real-time issue tracking and resolution. Through collaboration between academia and industry, the study explores the practical implementation of information technology solutions to enhance organizational communication and problem-solving. Results indicate improved communication efficiency and problem resolution within the organization, highlighting the potential of such systems to contribute to the evolution of information technology in the workplace. Highlights : Implementation of ETS module improves communication efficiency. Collaboration between academia and industry addresses practical challenges. Integration of technology enhances problem-solving within organizations. Keywords: Organizational Communication, Employee Tracking System, Information Technology, Logistics Industry, Collaboration